MPLS (Multi prortocol Label Switching) Applications - DELMI, Youssouf (My University, 2020)
List of Abbreviations ATM Asynchronous transfer mode ACL Access List BGP Border gateway Protocol CE Customer edge CEF Cisco Express Forwarding CSPF Constrained Shortest Path First DSCP Differentiated Services Code Point EGP Exterior getway protocol EIGRP Enhanced Interior Gateway Routing Protocol ERO Explicit Route Object ERP Entreprise resource planning EXP Experimental FIB Forwarding information base HDLC Level Data Link Control IGP Interior getway protocol LFIB Label Forwarding Info Base LDP Label Distribution Protocol LSR Label Switch Router LSA Link-state advertisement MPBGP Multi-Protocol Border gateway Protocol MPLS Multi protocol label switching NLRI Network Layer Reachability Information OSPF Open shortest path Firset PE Provider edge QoS Quality of services RIP Routing Information Protocol RSVP Resource Reservation Protocol SLA Service-level agreement TE Traffic Engineering TED Traffic Engineering Database TLV Type Length value ToS Type of service VoIP Voice over IP VPN Virtual Protocol Network WAN Wide area network Abstract This thesis will describe MPLS networks and explain the need for such technology as well as its contribution to networking in general. We focused on its major applications, how it can provide WAN connectivity between remote sites in a scalable way by implementing MPLS VPN, how we can optimize network infrastructure usage and manually prioritize traffic based on its nature within the MPLS network via TE and QoS. Finally, we deployed all the previous features separately in order to make our knowledge more tangible, for that we used GNS3 to get the closest results to real-world implementations, alongside WireShark to capture pertinent packets for demonstration purposes. Keywords: IP, VPN, MPLS, TE and QoS. Résumé Cette mémoire explique la technologie MPLS et sa nécessité dans les réseaux à grandes dimension, ainsi que ses applications principales afin de fournir une connectivité WAN entre les sites distants grâce à l’implémentation d’une architecture MPLS VPN, la manière d’optimiser l’utilisation d’une infrastructure réseau et comment tracer manuellement le trafic au sein d’un réseau MPLS via TE et QoS. Enfin, l’implémentation a été réalisée au moyen de simulateur GNS3 sur différentes topologie de réseau, et les tests en utilisant wireshark afin de capturer les paquets tout au long du chemin. Les mots clés : IP, MPLS, VPN et QoS. ملخص سوف نعالج في هذه المذكرة تقنية تبديل الوسوم متعدد البروتوكولات ونشرح الحاجة إلى هذه التقنية وكذلك مساهمتها في الإتصالات بشكل عام . ركزنا على تطبيقاتها الرئيسية وكيف يمكن أن توفر اتصال الشبكات الخاصة الإفتراضية ، كيف يمكننا تحسين استخدام البنية التحتية للشبكة وتحديد أولويات حركة البيانات يدويا مرتكزين على طبيعتها داخل الشبكة عبر جودة الخدمات.أخيرا،قمنا بتطبيق جميع الميزات السابقة بشكل منفصل من أجل جعل معرفتنا أكثر تطبيقية ، لذلك استخدمنا محاكي(GNS3) للحصول على النتائج لتطبيقات العالم الواقعي ، جنبا إلى جنب مع محلل البيانات ذات الصلة لغرض البرهنة . الكلمات المفتاحية : تبديل الوسوم متعدد البروتوكولات (MPLS) ،الشبكات الخاصة الافتراضية(VPN) ،جودة الخدمات (QoS) .
Keywords: IP; MPLS; VPN et QoS; réseaux